2016
DOI: 10.1007/s40415-016-0319-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of beneficial root pseudomonas on morphological, physiological, and phytochemical characteristics of Satureja hortensis (Lamiaceae) under water stress

Abstract: Water stress is the most important environmental factor that limits plant growth and yield. However, plant growth-promoting rhizobacteria (PGPR) can stimulate resistance of the plant host in unsuitable environmental conditions such as water stress. In order to evaluate whether PGPR improve morphological, physiological, and phytochemical traits of the savory plant Satureja hortensis L., the effects of two PGPR strains of Pseudomonas fluorescens Migula (PF-135 and PF-108) under two water conditions (well-watered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Mohammadi et al (2017) reported that inoculation of Satureja hortensis L. with P. fluorescens (PF-135) not only significantly increased the plant biomass and essential oil yields under water deficit stress condition but also improved the activity of antioxidant enzymes and synthesis of proline. Moreover, an investigation on corn inoculated with Pseudomonas spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mohammadi et al (2017) reported that inoculation of Satureja hortensis L. with P. fluorescens (PF-135) not only significantly increased the plant biomass and essential oil yields under water deficit stress condition but also improved the activity of antioxidant enzymes and synthesis of proline. Moreover, an investigation on corn inoculated with Pseudomonas spp.…”
Section: Discussionmentioning
confidence: 99%
“…The PGPR strains then were evaluated based on their ability to increase chamomile seedling growth index in a sand culture assay (data are not shown). Based on the results of this assay, the Pseudomonas fluorescens-135 (PF-135) was determined as the best pseudomonads strain (Mohammadi et al, 2017). Plant growth promoting activities of this strain are shown in Table 1. )…”
Section: Plant Growing Condition Treatments and Samplingmentioning
confidence: 99%
“…Peanut plants treated with halotolerant bacteria such as Klebsiella, Pseudomonas, Agrobacterium, and Ochrobactrum showed an increase in nitrogen (N 2 ) content up to 76% as compared to untreated peanut plants under salinity [112]. Water stress is the most important abiotic stress, which limits the plant growth and their yield, and can be controlled by PGPR that reduces the water stress by stimulating resistance of the host [113]. Plant under the water-stressed condition showed a reduction in the activity of ascorbate peroxidase (APX) and guaiacol peroxidase (GPX), but PGPR-associated water-stressed plants showed higher activity of GPX and APX, significantly [114,115].…”
Section: Effect Of Pgpr On the Oxidative Stress Enzymesmentioning
confidence: 99%
“…Water stress is the most important abiotic stress, which limits the plant growth and their yield, and can be controlled by PGPR that reduces the water stress by stimulating resistance of the host [113]. Plant under the water‐stressed condition showed a reduction in the activity of ascorbate peroxidase (APX) and guaiacol peroxidase (GPX), but PGPR‐associated water‐stressed plants showed higher activity of GPX and APX, significantly [114,115].…”
Section: Pgpr‐mediated Biochemical and Physiological Changes In The Hmentioning
confidence: 99%
“…Besides, microorganisms can act as elicitors and increase the production of secondary metabolites involved in the biological and pharmaceutical activity of medicinal plants (Mohammadi et al, 2017), such as flavonoids and terpenes content, phenolic compounds, microbial activity, chlorophyll content, nutrient uptake, plant growth and development (Banchio et al, 2008;Cappellari et al, 2013;Zhao et al, 2016;Damam et al, 2016;Swamy et al, 2016).…”
Section: Application Of Plant Growth Promoting Microorganismsmentioning
confidence: 99%